Government & Politics in Africa Prepared - Dr. Alier,; Bill, Dut Bol Ayuel (IJRDO - Journal of Social Science and Humanities Research, 2022)
Africa presents two faces. There is the Africa of lingering poverty, AIDS, intractable ethnic conflicts, irredeemable corruption, leadership failure and other social, economic and political ills. And there is the Africa of ancient history, rich traditional culture, Olympic soccer champions, Nobel Laureates, great economic potentials, and more. However, much of what is known about Africa today in the outside world, including the United States, is based on the former than the latter- thanks to inadequate scholarship and media bias that have encouraged public generalizations and misconceptions about the continent.  With the goal of providing an informed and balanced view of Africa, this course will consider a broad range of empirical and theoretical questions about the continent. Although we will touch on Africa’s colonial history and legacies, the focus will be on events from the second half of the 20th century (1950-2012), when nearly all contemporary African countries achieved political independence. We will explore varied sources of information to understand Africa’s socio-demographic, economic and political transformations over this period. It is hoped that at the end of this module, students will have gained capacity to analyze Africa objectively and broadened their global perspectives and to have mastered the trend and current state of politics and government in Africa Politics and Good Governance: with emphasis on democracy, human rights and ethics and National Integration in Africa.